2010
DOI: 10.1007/s10562-010-0292-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations and Catalytic Properties of Chromium Silicalite-2 Prepared by Direct Hydrothermal Synthesis and Impregnation

Abstract: A series of Cr-Si-2 molecular sieves have been prepared by direct hydrothermal synthesis using tetrabutylammonium hydroxide as a template. Cr/Si-2 was also prepared by conventional impregnation. The synthesized materials were characterized by X-ray diffraction (XRD), N 2 adsorption (-196°C), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR), and diffuse reflectance (UV-vis) spectroscopic measurements. Cr-Si-2 sample with lower content of chromium (ca.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Unlike ZSM-5 (MFI topology) with both straight and sinusoidal micropores, ZSM-11 only has straight channels. ZSM-11 has many applications in the aromatization and isomerization of 1-hexene [60][61][62], cracking of pentenes to C 2 -C 4 olefins [63,64], conversion of methanol to hydrocarbons [61,65,66], alkylation of benzene [67,68], and dehydrogenation of alkanes [69,70]. ZSM-11-based catalysts often show better performance than ZSM-5-based catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike ZSM-5 (MFI topology) with both straight and sinusoidal micropores, ZSM-11 only has straight channels. ZSM-11 has many applications in the aromatization and isomerization of 1-hexene [60][61][62], cracking of pentenes to C 2 -C 4 olefins [63,64], conversion of methanol to hydrocarbons [61,65,66], alkylation of benzene [67,68], and dehydrogenation of alkanes [69,70]. ZSM-11-based catalysts often show better performance than ZSM-5-based catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 showed the powder X-ray diffraction patterns for various MEL zeolite samples; it was observed that all the synthesized samples exhibited the characteristic peaks (such as 2θ = 7.9, 8.8, 14.8, 23.1, and 23.9 ) of an MEL topologic framework, 23,24 indicating that the MEL zeolites were successfully fabricated in the present work. No other detectable diffraction peaks for metal phases, such as large iron oxides, were found, which indicated a substantial absence of large metal crystallites.…”
Section: Characterization Of Zeolitesmentioning
confidence: 77%
“…Cr-Si-2 molecular sieve catalyst with 1.28 wt% chromium gave 45.5% ethylene yield with a selectivity of 87.9% at 650°C. The change of Cr from a higher oxidation state to lower oxidation state was found to influence the catalyst behavior [12]. The ODH of ethane with CO 2 was successfully carried out over the Cr-based catalysts prepared by using FeCrAl alloy foil as support [13] [19].…”
Section: Catalytic Activitymentioning
confidence: 99%
“…5-8 wt% Cr 2 O 3 /SiO 2 catalysts have exhibited excellent performance [6,11]. However, the aggregation of CrO x on SiO 2 is found to negatively influence the catalyst behavior, particularly during the reaction on Cr-Si-2 molecular sieve catalyst [12]. SBA-15 is later found to be a convenient support to overcome the problem of aggregation [13].…”
Section: Introductionmentioning
confidence: 99%